PENGEMBANGAN SISTEM INFORMASI SURVEILANS INFEKSI TERKAIT PELAYANAN KESEHATAN DENGAN METODE WATERFALL - Prasetya, Rhesa (Universitas Methodist Indonesia, 2024)
Healthcare-associated infections (HAIs) are infections that occur when patients receive healthcare in a hospital or another healthcare facility. These infections can jeopardize patient safety, induce illness, and potentially lead to fatal outcomes. Prevention of HAIs involves the implementation of robust healthcare-associated infection surveillance practices and infection prevention and control measures. Surveillance activities, encompassing manual recording, daily monitoring, and manual reporting, may consume nursing time and pose a potential risk of inaccuracies. Therefore, we have undertaken the design of a healthcare-associated infection surveillance information system using the waterfall methodology. The information system has been developed using PHP language and a MySQL database. The deployment of this system aims to streamline and enhance the precision of record-keeping. The analytical insights derived from its reports can be harnessed to mitigate the incidence of healthcare-associated infections.